2019
DOI: 10.1038/s41377-018-0113-y
|View full text |Cite
|
Sign up to set email alerts
|

Interference-assisted kaleidoscopic meta-plexer for arbitrary spin-wavefront manipulation

Abstract: Achieving simultaneous polarization and wavefront control, especially circular polarization with the auxiliary degree of freedom of light and spin angular momentum, is of fundamental importance in many optical applications. Interferences are typically undesirable in highly integrated photonic circuits and metasurfaces. Here, we propose an interference-assisted metasurface-multiplexer (meta-plexer) that counterintuitively exploits constructive and destructive interferences between hybrid meta-atoms and realizes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 160 publications
(76 citation statements)
references
References 44 publications
(28 reference statements)
1
75
0
Order By: Relevance
“…It is observed that the conversion coefficient from RCP incidence to the LCP component (i.e., focusing component) in the transmitted field is ≈20% (Figure a) while the conversion coefficient from LCP incidence to the LCP component (focusing component) in the reflected field is ≈75% (Figure b). The cross‐polarized conversion coefficient of the focusing component in either transmitted or reflected field is comparable to those reported to be obtained using either a double‐split ring resonator or a chiral‐stepped nanoaperture structure . Details regarding the polarization conversion in the reflection field for RCP and LCP incidences are given in Supplementary S2 (Supporting Information).…”
Section: Theory and Structure Designsupporting
confidence: 71%
See 1 more Smart Citation
“…It is observed that the conversion coefficient from RCP incidence to the LCP component (i.e., focusing component) in the transmitted field is ≈20% (Figure a) while the conversion coefficient from LCP incidence to the LCP component (focusing component) in the reflected field is ≈75% (Figure b). The cross‐polarized conversion coefficient of the focusing component in either transmitted or reflected field is comparable to those reported to be obtained using either a double‐split ring resonator or a chiral‐stepped nanoaperture structure . Details regarding the polarization conversion in the reflection field for RCP and LCP incidences are given in Supplementary S2 (Supporting Information).…”
Section: Theory and Structure Designsupporting
confidence: 71%
“…Imaging elements and polarization manipulation elements have been the two of the most widely investigated device types because of the essential and indispensable functions of these elements . In contrast with the traditional bulky optical lenses, a metalens is a micro/nanostructured metasurface lens in which the amplitude, phase, and polarization state of the transmitted or reflected electromagnetic waves can be manipulated by the micro/nanostructures at the subwavelength scale based on the effects of surface plasmonic polaritons (SPP) or localized surface plasmonics (LSP), Mie resonances, and geometric phase (also known as Pancharatnam–Berry phase, P–B phase), using which focusing, imaging and/or wavefront manipulation in the transmission or reflection can be achieved. Plasmonic lenses consist of an array of metal plasmonic antennas in which a phase discontinuity related to the geometry and dimension of the metallic antennas appears between the incident electromagnetic wave and the transmitted and/or reflected electromagnetic wave due to the SPP/LSP effects.…”
Section: Introductionmentioning
confidence: 99%
“…Metasurfaces, the 2D version of MTMs, are drawing more and more attention and have become the new hot spot in the research of MTMs . Governed by the generalized Snell's laws of reflection and refraction, the abrupt phase changes on the interface as well as the surface impedances are modulated so as to realize desired functionalities, such as the manipulating the polarization of EM waves, holographic imaging and transforming wavefronts . It has also been used in the conversion of spatially propagating waves to surfaces waves .…”
Section: Metasurfaces and Other State‐of‐the‐art Microwave Mtmsmentioning
confidence: 99%
“…In general, metasurfaces are constructed by arranging the different amplitudes and phases of each minimum pixel on a surface by changing the sizes or geometries of each meta‐atom to meet preset conditions and obtain desired field distribution for specific characteristics. [ 26–32 ] Another feasible method to construct multifunctional metasurfaces is to load tunable devices such as graphene, [ 33 ] diodes, [ 34,35 ] or microelectromechanical systems. [ 36 ] However, compared with passive metasurfaces, some limitations still exist, including complicated design, high insertion loss, and poor robustness.…”
Section: Introductionmentioning
confidence: 99%